A systematic review of dramatherapy interventions used to alleviate emotional distress and support the well‐being of children and young people aged 8-18 years old - Eleanor Keiller; Megan Tjasink; Jane Bourne; Dennis Ougrin; Catherine Elizabeth Carr; Jennifer Y. F. Lau (Wiley, 2023)
Abstract Background Dramatherapy, a creative form of psychotherapy, may be a useful treatment for child and adolescent mental health. As there is a growing evidence base, this systematic review sought to identify, describe and evaluate dramatherapy with children and adolescents who were experiencing emotional distress (anxiety, depression and trauma) in order to inform future research in this area. Methods Seven databases (PsychInfo, PubMed, Scopus, Web of Science, CINAHL, EMBASE and Cochrane) were searched for peer‐reviewed articles exploring dramatherapy as a treatment for child and adolescent emotional distress. Hand searches of relevant journals were also conducted. Two reviewers coded articles for eligibility and independently appraised papers using the Joanna Briggs Institute Critical Appraisal Tools. Details relating to intervention and participant characteristics were extracted and, where data were available, effect sizes on measures relating to emotional distress were calculated. Results Fifteen papers were included. Studies showed that dramatherapy was often delivered in schools (46%) and clinical settings (20%) and was more frequently delivered to adolescents (53%) (>11 years) than children (26%) (8-11 years). Dramatherapy was used as a treatment for diagnostically heterogeneous groups (40%), for emotional and behavioural difficulties (33%) and following a shared, traumatic, experience (20%). Seven papers reported relevant quantitative data however, just three of these studies were controlled and none were blinded. Pre‐to‐post intervention effect sizes ranged from d = 0.17 to d > 2 yet samples were small and participant response to treatment was not always consistent. The largest effects were seen in dramatherapy employed following trauma and in clinical settings. Medium to large effects were also seen in early intervention school‐based dramatherapy. Conclusion Despite promising results with regards to the treatment of child and adolescent emotional distress, the evidence base for dramatherapy is small and methodologically flawed. Larger, methodologically robust trials should test the efficacy of dramatherapy in future research.